Melindungi dan Menjaga Situs Bersejarah di Kecamatan Natal, Kabupaten Mandailing Natal - Siregar, Putri Khofifah; Monang, Sori; Nasution, Kasron (Medan Resource Center, 2024)
This article aims to discuss the preservation and conservation of historical sites in Natal District, Mandailing Natal Regency. The Mandailing Natal region boasts a wealth of cultural heritage in the form of various historical sites. However, the current condition of these historical structures is deeply concerning, necessitating urgent restoration and maintenance efforts. This article employs a qualitative research approach with a descriptive method. The research methodology utilized the historical method, consisting of four stages: heuristics, verification or criticism, interpretation, and historiography. The research findings reveal that the local community, including the Department of Culture and Tourism, has started to recognize the significance of historical sites in Natal District. Nevertheless, concrete measures to safeguard and preserve the heritage within the Mandailing Natal region, particularly in Natal District, have yet to materialize. Therefore, an active role from both the community and the government is imperative to protect and conserve these historical relics, ensuring that they can be cherished by future generations.